PARTISIPASI GAPOKTAN MULYO ASRI DI DESA JENGGRIK KABUPATEN NGAWI UNTUK PENGENDALIAN HAMA DAN PENYAKIT KEDELAI BERBAHAN KULIT BIJI JAMBU METE - Wuye Ria Andayanie; Indah Rekyani Puspitawati; Ratna Mustika Wardhani (UNIVERSITAS PGRI MADIUN, 2025)
Abstract. Participation comunication for soybean farmers is carried out to reduce the use of chemical pesticides is absolutely necessary in sustainable and environmentally friendly agricultural activities. Farmer extension in community-based service activities aims to determine the level of farmer participation in the implementation of pest and disease control programs on cashew nut shell plants. The method of implementing community-based service uses purposive sampling. Samples were taken from 28 respondents from the Gapoktan